Analisis Faktor-Faktor Yang Mempengaruhi Impor Gandum Indonesia - Novaninda Ayu Cipta; Kiky Asmara (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
Indonesia must provide for its residents' food demands because of its expanding population. Due to limitations in producing it, Indonesia imports a lot of wheat to meet the consumption need. This research attempts to: 1) examine some factors that affecting indonesia wheat import 2) to analyze the effect of dollar exchange rate, global wheat price, and indonesian wheat consumption on Indonesian wheat imports. This study used secondary data in the form of dollar exchange rate, global wheat price, and indonesian wheat consumption for the last 23 years (2000-2022). Eviews 12.0 was used to process the data, and multiple linear regression models with the Ordinary Least Square (OLS) technique were used. The multiple linear regression findings demonstrate that only Indonesian wheat consumption has a positive impact on imports of Indonesian wheat; the impact of the dollar exchange rate and the world wheat price is negligible.